A historical review of the controversy over U.S. corporate investments in apartheid South Africa, 1960–1994 - Ncube, Godfrey Tabona (Midlands State University, 2016)
In 2014 a group of plaintiffs in the U.S. brought a lawsuit against U.S. corporations that had had business investments in South Africa during the apartheid era from the 1960s to the 1990s, on the grounds that their investments had provided material support for race-based human rights abuses in that country. This lawsuit, which was presented before a U.S. District Judge in Manhattan, Shira Scheindlin, was reviving a 12-year old case that sought to hold U.S. corporations liable for aiding and abetting the apartheid regime in perpetrating abuses, such as killings and torture. The plaintiffs contended that by supplying military vehicles and computers to the South African security forces, the U.S. companies had violated international law by encouraging human rights abuses (Sunday News Business, April, 2014). They argued that the U.S. companies had reinforced the apartheid regime materially by providing much-needed capital, technology and trade contacts which were critical to regime maintenance. This paper explores the long and chequered history of this controversy that bega in the 1960s that provides the background for this litigation that now seeks compensation for apartheid era human rights violations, with potential damages in billions of dollars. It reviews this controversy by making a critical examination of the ‘progressive force’ argument that was proffered by U.S. corporations between 1960 and 1994 as a justification for investment in South Africa; against the argument presented by churches and civic society for disinvestment and withdrawal. It explores issues related to corporate social responsibility and social policy, and interrogates the U.S. companies’ economic thesis that the introduction of business reforms at the corporations’ South African plants would ultimately undermine racial segregation, and destroy apartheid, through an improvement in the contractual status of blacks in the labour force.